Motivation Theory in Education: Influence, Impact, and Application in the Classroom - Devita Paramesti; Aqela Naura Zavisa (Konsultan Jurnal Ilmiah Indonesia, 2025)
Learning motivation is a crucial factor that influences students' success in the learning process. This research aims to identify the influencing factors and their impact on academic achievement. The method used in this research is literature study, which collects and analyzes data, including scientific journals and related reference books. The research results show that internal learning motivation includes one's own interest, learning goals, and self-confidence, while external factors include rewards and praise, the school environment, and educators' teaching methods. Apart from that, it was also found that a positive learning environment and social support from educators and students play an important role in maintaining students' learning motivation. With these findings, a holistic approach is recommended in increasing learning motivation, to encourage better academic achievement.